Product Differentation, Harga Kompetitif, Service Delivery Increasing Purchase Decision : The Mediating Role of Social Media A Case study at Mujigae Dukuh Zamrud - Gesyke Julfani Endarto; Parlagutan Silitonga (LPPM Universitas Asa Indonesia, 2023)
The purpose of this study was to determine the infulence of Product Differentiation, Competitive Prices, Service Delivery, on Purchase Decisions Through Social Media at Mujigae Korean Food Delivery Dukuh Zamrud. The population in this study were all consumers of Mujigae Korean Delivery Dukuh Zamrud, using a accidental sampling technique with 201 respondents, and using a quantitative method by distributing questionnaires to consumers of Mujigae Korean Delivery Dukuh Zamrud, and data analysis using SmartPLS 3.2.9. The results obtained in this study are Product Differentiation has an effect, and Competitive Prices has an effect, and Service Delivery has no effect on Social Media. Whereas on Purchase Decision the Product Differentiation variable has an influence, Competitive Prices have no effect and Service Delivery has no influence, and Social Media has an influence.